PERANCANGAN KONTEN SEBAGAI SARANA PROMOSI MUSEUM TEKSTIL JAKARTA - Sinta Paramita; Laura Lauw; Marilyn Alexande; Nerissa Arviana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2023)
The museum is an institution whose function is to protect, develop, utilize collections, and communicate them to the public. The Textile Museum is a museum which was inaugurated by Mrs. Tien Suharto on June 28, 1976. The location of this research was the Jakarta Textile Museum. This study aims to promote the Textile Museum on social media. The Textile Museum has problems in communication, namely fewer teenage visitors tend to come and most of the visitors only come from school children who happen to get assignments. By looking at the problems faced by the Textile Museum, our team conducted the PKM Faculty of Communication Sciences, University of Tarumanagara to create a video content entitled